The long cosmos - Pratchett, Terry; Baxter, Stephen (Pratchett, Terry. Long Earth series., 2016)
The Next--the hyper-intelligent post-humans--realize that the missive they received from the center of the galaxy contains instructions for kick-starting the development of an immense artificial intelligence knows as The Machine. But to build this computer the size of an Earth continent, they must obtain help from the more populous and still industrious worlds of mankind.